Bioorthogonal double-fluorogenic siliconrhodamine probes for intracellular super-resolution microscopy - Kozma, Eszter; Lemke, Edward A. (Chemical communications, 2017)
A series of double-fluorogenic siliconrhodamine probes were synthesized. These tetrazine-functionalized, membrane-permeable labels allowed site-specific bioorthogonal tagging of genetically manipulated intracellular proteins and subsequent imaging using super-resolution microscopy.
Gesehen am 21.09.2018